The Relationship between Diet and Iron Deficiency Anemia in Post Partum Mothers in Dr. Zainoel Abidin Banda Aceh in 2019 - Aida Fitri; Darmawati; Mariatul Kiftia; Mira Rizkia; Syahbandi (Unit Penelitian dan Pengabdian Masyarakat STIKES Fatmawati Jakarta, 2020)
One of the problems that contributed the largest numbers on mortality and maternal morbidity was anemia in the postpartum period. It is estimated that 50-80% of women suffer from anemia at 48 hours after birth. Anemia in women is associated with increased birth Infant Low Birth Weight (LBW), prematurity, maternal and child deaths and infections. This study aims to identify the relationship between dietary patterns and the incidence of iron deficiency anemia in post partum mothers at dr. Zainoel Abidin hospital Banda Aceh. This research is a quantitative study with a cross sectional study design. This research was conducted from June to September 2019 with 102 respondents selected through the non-probability sampling method. Respondents were postpartum mothers who were treated in room 2 (obstetric inpatient room). The study technique was carried out by giving a questionnaire and hemoglobin check has been carried out using HB meter. The data obtained were analyzed using the chi square statistical test with a confidence level of 95%. This study found that the prevalence of anemia was 49,0% of respondents had mild anemia (Hb levels 9-10,9 gr / dl), 10,8% had moderate anemia (Hb levels 7-8,9 gr / dl), and 40,2% not having anemia (Hb levels >11gr / dl). Overall, there is a significant relationship between dietary patterns and the incidence of anemia in postpartum mothers at dr. Zainoel Abidin Banda Aceh (p value 0,032).